Mi Fu’s Concepts of Art Authentication and Their Ming–Qing Reception (Journal of Global Arts Studies, 2025)
Background: Mi Fu, the “Doctor of Calligraphy and Painting” of the Northern Song dynasty, was renowned for both his calligraphy and connoisseurship. His works Shushi (History of Calligraphy) and Huashi (History of Painting) circulated widely in the Ming and Qing through multiple editions, undergoing simultaneous processes of academic canonization and cultural mythologization. Objective: This study clarifies the core structure of Mi Fu’s authentication concepts and examines their reception and transformation in the Ming and Qing dynasties through texts, practices, and the remaking of his persona. Methods: Employing a sociology of text and cultural semiotics approach, the study traces the reception of Mi Fu's concepts through three interconnected trajectories: the textual canonization from individual experience to cataloguing norm; the personal mythologization from historical figure to cultural symbol; and the differentiation of collectors from aesthetic distinction to social stratification. This tripartite path underscores the dynamic interplay between scholarly discourse, cultural imagination, and social practice in the evolution of Chinese art connoisseurship. Results: Mi Fu developed a comprehensive language of authentication that included brushwork, mounting, transmission records, and seals. This framework became the direct catalogue norm and discursive blueprint for Ming-Qing connoisseurship, underscoring its shift "from experience to canon." His discourse not only shaped the value spectrum distinguishing the "true connoisseur" from the "mere dilettante" but also provided a methodological foundation for later catalogues and connoisseurial practices. Conclusion: Mi Fu not only laid the foundation for Chinese calligraphy and painting authentication but, through Ming-Qing reinterpretations, also completed the transformation from experience to canon, from text to market, and from historical figure to cultural myth, becoming a central coordinate in the history of Chinese art connoisseurship.
Keywords: Mi Fu; Calligraphy and Painting Authentication; Textual Transmission; Mythologization